Assessing chemical exposure risk in breastfeeding infants: An explainable machine learning model for human milk transfer prediction - Xiaojie Huang; Jiajia Chen; Peineng Liu (Ecotoxicology and Environmental Safety)
Breast milk is essential for infant health, but the transfer of xenobiotic chemicals poses significant risks. Ethical challenges in clinical trials necessitate the use of in vitro predictive models to assess chemical exposure risks in breastfeeding infants. This study introduces an explainable machine learning model to predict the risk of chemical transfer through human milk. Our novel framework integrates ensemble resampling methods with advanced feature selection techniques, addressing data imbalance and enhancing predictive accuracy. The balanced random forest classifier, optimized using the genetic algorithm for feature selection, achieved an area under the receiver operating characteristic curve (AUC) of 0.8708 and an accuracy of 82.67 % on the internal test set, with an accuracy of 86.36 % on the external validation set. The integration of the SHapley Additive exPlanations approach provided deeper insights by revealing how specific chemical properties influence the transfer of high-risk compounds into breast milk. This enhanced interpretability offers a clearer understanding of the associated risks and informs strategies for their mitigation. Structural alert analysis further identified molecular fragments linked to high-risk chemicals, enabling targeted risk assessments. Additionally, the model was applied to evaluate the transfer risks of FDA-approved drugs from 2019 to 2024, identifying several with high transfer probabilities. To broaden its application, we developed an online prediction tool that offers real-time risk assessments, providing an accessible resource for healthcare professionals and researchers. These contributions present a robust, ethically sound tool for assessing chemical exposure risks in breastfeeding infants, supporting informed decisions on drug use and environmental contaminant exposure.